Current collector, electrode sheet, secondary battery, electric device, and copper foil and method for producing the same
Patent Information
- Application Number
- CN202480005930.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-01
- Filing Date
- 2024-08-26
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-08-26
AI Technical Summary
[0071]该铜箔能够实现大尺寸制造,具有工业化应用的前景。
Smart Images

Figure CN120787380B_ABST
Abstract
Description
[0001] Cross-references
[0002] This application incorporates Chinese Patent Application No. 202410146761.1, filed on February 1, 2024, entitled “Current collector, electrode, secondary battery, electrical device, copper foil and method for preparing the copper foil”, which is incorporated herein by reference in its entirety. Technical Field
[0003] This application belongs to the field of battery technology, specifically relating to a current collector, an electrode, a secondary battery, an electrical device, a copper foil, and a method for preparing the copper foil. Background Technology
[0004] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric cars, military equipment, and aerospace.
[0005] Current collectors are an important component of rechargeable batteries. With increasing market demands for higher energy density and safety performance in rechargeable batteries, there is an urgent need to develop lightweight and high-strength current collectors to meet the needs of next-generation rechargeable batteries. Summary of the Invention
[0006] This application is made in view of the above-mentioned issues, and its purpose is to provide an ultra-thin current collector with excellent mechanical properties to meet the requirements of the next generation of high-performance batteries for current collectors.
[0007] To achieve the above objectives, this application provides a current collector, an electrode, a secondary battery, an electrical device, a copper foil, and a method for preparing the copper foil.
[0008] The first aspect of this application provides a current collector comprising a copper foil, wherein the average grain size of the grains in the copper foil is 50nm-400nm, and the proportion of nanotwins is not less than 60% based on the total number of grains in the copper foil.
[0009] Twin structures are an effective means of improving the strength and ductility of metals. Twin boundaries are coherent interfaces with orderly atomic arrangement, which can increase material strength by enhancing the resistance to dislocation movement while maintaining dislocation mobility, thus preserving the material's ductility while strengthening it. Small grain size can further increase the interface structure, raising the external stress required for dislocations to cross grain boundaries, thereby achieving material strengthening. The combined effect of a high proportion of nanotwin structures and small grain size is beneficial for improving the mechanical strength of copper foil while maintaining its high ductility, providing a material basis for further improvements in battery energy density and safety.
[0010] In any embodiment, the average grain size of the copper foil is 50nm-300nm.
[0011] Copper foil with an average particle size within the above range can further improve its mechanical strength while maintaining the high plasticity of copper foil, thus meeting the application requirements of the new generation of high energy density secondary batteries.
[0012] In any embodiment, based on the total number of grains in the copper foil, the proportion of grains with a diameter less than 200 nm is 20%-40%, and the proportion of grains with a diameter between 200 nm and 500 nm is 50%-80%.
[0013] In any embodiment, based on the total number of grains in the copper foil, the proportion of grains with a diameter greater than 500 nm is less than or equal to 5%.
[0014] In existing technologies, copper foil reinforced by twinning often introduces micron-sized twins during the fabrication process, hindering further improvement in copper foil strength. The copper foil provided in this application has a high proportion of nanotwins, significantly improving its strength. Furthermore, the grains have a small average particle size and a skewed distribution, with very few grains larger than 500 nm. This fine grain structure reduces stress concentration during copper foil deformation and promotes grain-to-grain slip, thus improving both copper foil strength and elongation at break.
[0015] In any embodiment, based on the total number of grains in the copper foil, the proportion of equiaxed grains or quasi-equiaxed grains is greater than or equal to 80%, and the ratio a1 of the major axis to the minor axis of the equiaxed grains or quasi-equiaxed grains satisfies: 1≤a1<2.
[0016] A large number of equiaxed or equiaxed grains are beneficial for achieving isotropy of copper foil in all directions, and for comprehensively improving the strength and plasticity of copper foil.
[0017] In any embodiment, based on the total number of grains in the copper foil, the proportion of columnar grains is less than 10%, and the ratio a2 of the major axis to the minor axis of the columnar grains satisfies: a2 > 2.
[0018] The formation of columnar grains easily leads to anisotropy in the mechanical properties of copper foil. Reducing the proportion of columnar grains is beneficial to improving the mechanical strength and plasticity of copper foil and reducing the probability of stress concentration points.
[0019] In any embodiment, the diffraction intensity of the (111) texture in the copper foil accounts for 60%-85% of the total diffraction intensity of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil.
[0020] For pure copper materials, common textures include (111), (200), (220), (311), and (222). According to crystallographic properties, the (111) crystal plane has a high atomic density and high mechanical strength, which can improve the twinning strengthening effect. Copper foils with a crystal plane diffraction intensity of (111) texture relative to the sum of the crystal plane diffraction intensities of (111), (200), (220), (311), and (222) textures within the above range are beneficial to improving the mechanical strength and plasticity of copper foils.
[0021] In any embodiment, the copper foil has a first surface and a second surface opposite to each other, the thickness of the copper foil is denoted as H, the region from the first surface of the copper foil to a thickness range of 0.2H-0.5H is denoted as the first region of the copper foil, and the region from the second surface of the copper foil to a thickness range of 0.2H-0.5H is denoted as the second region of the copper foil, wherein the absolute value of the difference between the average grain size of the grains in the first region and the average grain size of the grains in the second region is less than or equal to 150 nm.
[0022] The grain size and structure of the copper foil are highly uniform along the thickness direction, which provides a basis for maintaining high strength and high ductility while having an ultra-thin thickness.
[0023] In any embodiment, the proportion of nanotwins in terms of the total number of grains in the copper foil is 65% to 90%.
[0024] In any embodiment, the maximum surface roughness of the copper foil is less than or equal to 3 μm.
[0025] Copper foil with a maximum surface roughness of no more than 3μm has a smooth and uniform surface, which makes it less likely to form stress concentration points during cyclic stress, thus improving the mechanical strength and plasticity of the copper foil.
[0026] In any embodiment, the thickness H of the copper foil satisfies: 3μm≤H≤15μm.
[0027] The copper foil has a low thickness, which enables effective weight reduction of the battery and is conducive to further improving the battery's energy density.
[0028] In any embodiment, under test conditions of room temperature, sample thickness of 6±0.2μm, and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is greater than or equal to 600MPa and the elongation at break of the copper foil is greater than or equal to 4%.
[0029] In any embodiment, under test conditions of room temperature, sample thickness of 6±0.2μm, and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is 700MPa-1500MPa; the elongation at break of the copper foil is 4.5%-10%.
[0030] The aforementioned copper foil possesses both high strength and high plasticity, which can meet the requirements of high energy density batteries, improving battery safety while increasing battery energy density.
[0031] A second aspect of this application provides an electrode including a current collector in any embodiment.
[0032] A third aspect of this application provides a secondary battery, including the electrode of the second aspect.
[0033] In any embodiment, the secondary battery is any one of a battery cell, a battery module, or a battery pack.
[0034] In any embodiment, the maximum expansion force of the secondary battery cell is greater than or equal to 1000 kgf.
[0035] In any embodiment, the maximum expansion force of the secondary battery cell is greater than or equal to 2500 kgf.
[0036] In any embodiment, the maximum expansion force of the secondary battery cell is greater than or equal to 4000 kgf. Current collectors in the prior art are prone to fracture under the high expansion force of secondary batteries, leading to safety accidents and limiting further improvements in the electrochemical performance of secondary batteries. The current collector provided in this application possesses both excellent tensile strength and elongation at break, making it suitable for secondary batteries with high expansion forces and beneficial for further improving the energy density of secondary batteries.
[0037] A fourth aspect of this application provides an electrical device including a secondary battery as described in the third aspect.
[0038] The fifth aspect of this application provides a method for preparing copper foil, wherein the copper foil is prepared by electroplating. The electroplating method specifically includes periodically applying an electric current to an electroplating solution, causing copper ions in the electroplating solution to be reduced and deposited to form copper foil. The average grain size of the copper foil is 50 nm to 400 nm, and based on the total number of grains in the copper foil, the proportion of nanotwins is greater than or equal to 60%.
[0039] In any implementation, the current is a pulse current, which includes one or more of square wave pulse current, sine wave pulse current, triangular wave pulse current, and sawtooth wave pulse current.
[0040] Applying a pulsed current to the electroplating solution allows for control over the nucleation of reduced copper ions and grain growth by switching the current on and off. This suppresses grain growth, resulting in uniform nanocrystals and improving the tensile strength and elongation at break of the copper foil. Compared to the commonly used direct current deposition technology, pulsed current deposition can achieve a higher peak current density, which is beneficial for the extensive nucleation of copper foil, thereby increasing its density and reducing its grain size to improve its mechanical strength.
[0041] In any embodiment, the electroplating solution includes additives, which include one or more of leveling agents, wetting agents, and brighteners.
[0042] In any embodiment, the additive includes a leveling agent, a wetting agent, and a brightening agent.
[0043] Leveling agents can adhere to the tips of copper foils with high deposition rates, inhibiting grain growth, balancing the growth rates of pits and tips, and improving the flatness of the copper foil. Wetting agents can improve the wettability of the plating solution and the substrate. The wettability of the plating solution on the cathode is sufficient to enable rapid electrodeposition with high current, increasing the nucleation rate of the copper foil and reducing the average grain size in the copper foil. A certain amount of brightener can make the grain size of the copper foil even smaller, reduce the surface roughness of the copper foil, and improve the surface smoothness.
[0044] In any embodiment, the concentration of the leveling agent in the electroplating solution is 20 mg / L-300 mg / L.
[0045] In any embodiment, the concentration of the leveling agent in the electroplating solution is 50 mg / L-150 mg / L.
[0046] In any embodiment, the concentration of the wetting agent in the electroplating solution is 10 mg / L-200 mg / L.
[0047] In any embodiment, the concentration of the wetting agent in the electroplating solution is 30 mg / L-100 mg / L.
[0048] In any embodiment, the concentration of the brightener in the electroplating solution is 10 mg / L-200 mg / L.
[0049] In any embodiment, the concentration of copper ions in the electroplating solution is 30 g / L to 100 g / L.
[0050] In any embodiment, the concentration of copper ions in the electroplating solution is 45 g / L to 75 g / L.
[0051] The results show that a combination of low copper ion concentration and high additive concentration is more beneficial to improving the overall strength and elongation at break of copper foil than a combination of high copper ion concentration and low additive concentration. Furthermore, a low copper ion concentration helps reduce concentration polarization, control grain growth and deposition rates, which is conducive to preparing small-sized grains and improving the mechanical strength of the copper foil.
[0052] In any embodiment, the concentration of chloride ions in the electroplating solution is 10 mg / L-80 mg / L.
[0053] In any embodiment, the pH of the electroplating solution is 2.5-4.4.
[0054] In any embodiment, the leveling agent includes one or more of gelatin and Janus Green; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; and the brightening agent includes one or more of sodium dithiodipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and thiourea.
[0055] In any embodiment, the wetting agent includes hydroxyethyl cellulose and polyethylene glycol.
[0056] The results show that adding two different wetting agents simultaneously can more effectively improve the mechanical strength of copper foil compared to adding a single type of wetting agent. Although the mechanism is not yet clear, it is speculated that it may be related to the competitive adsorption of the two different types of additives, which is beneficial to improving the uniformity of grains during the deposition process, reducing the difference in grain size in the thickness direction, and improving the uniformity of copper foil.
[0057] In any embodiment, the mass concentration ratio of the copper ions to the leveling agent is 500:1-4500:1; and / or, the mass concentration ratio of the copper ions to the brightener is 300:1-6000:1.
[0058] In some embodiments, the electroplating solution includes gelatin at a concentration of 20 mg / L-150 mg / L, polyethylene glycol at a concentration of 15 mg / L-100 mg / L, hydroxyethyl cellulose at a concentration of 10 mg / L-80 mg / L, sodium polydisulfide dipropane sulfonate at a concentration of 15 mg / L-150 mg / L, copper ions at a concentration of 45 g / L-90 g / L, and chloride ions at a concentration of 10 mg / L-80 mg / L.
[0059] In any embodiment, the peak current density of the pulse current is I, in A / dm². 2 The duty cycle of the pulse current is s, and the peak current density I satisfies the condition 2A / dm². 2 ≤I×s≤18A / dm 2 .
[0060] The product of the peak current density I and the duty cycle s corresponds to the average current density within the pulse period. Pulsed deposition allows the average current density within the pulse period to be higher than the maximum current density achievable with direct current deposition, because excessively high direct current deposition densities can lead to hydrogen evolution and concentration polarization in the plating solution, reducing the uniformity of the copper foil during electrodeposition. The product of the peak current density I and the duty cycle s within the aforementioned range can effectively reduce grain size and improve the uniformity of grain size in the thickness direction of the prepared copper foil. The combination of the peak current density I and the duty cycle s within the aforementioned range, along with a low copper ion concentration in the plating solution, can further improve the concentration polarization phenomenon of the plating solution, enabling the preparation of small-sized grains and improving the tensile strength and elongation at break of the copper foil. In any embodiment, the peak current density I of the pulsed current satisfies: 3.3 A / dm² ≤ I ≤ 333 A / dm².
[0061] In any implementation, the duty cycle s of the pulse current satisfies: 2% ≤ s ≤ 50%.
[0062] In any implementation, the pulse width of the pulse current is 1ms to 50ms.
[0063] In any embodiment, the distance between the cathode electrode and the anode electrode is 15mm to 20mm.
[0064] In any embodiment, the deposition temperature is 45°C-60°C.
[0065] In any implementation, the deposition time is greater than or equal to 80 seconds.
[0066] In any embodiment, the electroplating method specifically includes periodically applying a pulsed current to the electroplating solution to reduce and deposit copper ions in the electroplating solution; wherein the peak current density I of the pulsed current satisfies 100A / dm²≤I≤180A / dm², the duty cycle s of the pulsed current satisfies 2%≤s≤10%, and the deposition time is 80s-250s.
[0067] In any embodiment, the preparation method is a continuous production method.
[0068] A sixth aspect of this application provides a copper foil that includes the same features as the copper foil in the aforementioned current collector, which will not be repeated here.
[0069] In any embodiment, the copper foil is prepared by the preparation method of the fifth aspect.
[0070] In any embodiment, the maximum width of the copper foil is greater than or equal to 1.5 meters, and / or the maximum length of the copper foil is greater than or equal to 10,000 meters.
[0071] This copper foil can be manufactured in large sizes and has the potential for industrial applications. Attached Figure Description
[0072] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0073] Figure 1 This is a schematic diagram of the grain size distribution of the copper foil in Embodiment 1 of this application; Figure 2 This is the inverse pole figure of the electron backscatter diffraction image of the copper foil of Embodiment 1 of this application; Figure 3 This is a stretching curve of the copper foil in Embodiment 1 of this application; Figure 4 a is the X-ray diffraction pattern of the copper foil in Embodiment 2 of this application; Figure 4 b is the X-ray diffraction pattern of the copper foil of Comparative Example 1 of this application; Figure 5 This is a schematic diagram of one embodiment of the secondary battery of this application; Figure 6 This is an exploded view of one embodiment of the secondary battery of this application; Figure 7 This is a schematic diagram of one embodiment of the battery module of this application; Figure 8 This is a schematic diagram of one embodiment of the battery pack of this application; Figure 9 yes Figure 8 An exploded view of an embodiment of the battery pack shown; Figure 10 This is a schematic diagram of one embodiment of an electrical device that uses a secondary battery as a power source, as described in this application. The accompanying drawings are not necessarily drawn to scale. The reference numerals are as follows: 1 Battery pack, 2 Upper casing, 3 Lower casing, 4 Battery module, 5 Secondary battery, 51 Housing, 52 Electrode assembly, 53 Cover plate. Detailed Implementation
[0074] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the current collector, electrode, secondary battery, electrical device, copper foil, and method for preparing the copper foil of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for a thorough understanding of this application by those skilled in the art and are not intended to limit the subject matter of the claims.
[0075] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0076] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.
[0077] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.
[0078] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0079] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0080] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0081] Unless otherwise specified, the terms used in this application have the common meanings as commonly understood by those skilled in the art.
[0082] Unless otherwise specified, the values of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, such as the testing methods provided in this application. Specifically, during the testing process, the microstructure of the copper foil as a whole is characterized by the sampling area.
[0083] Unless otherwise specified, in this application, the term "active ion" refers to ions that can be inserted and extracted back and forth between the positive and negative electrodes of a secondary battery, including but not limited to lithium ions.
[0084] In this application, the terms "multiple" or "various" refer to two or more kinds.
[0085] With the increasing energy density of rechargeable batteries, there is a growing demand for thinner and lighter current collectors. However, as the current collector becomes thinner, its maximum load-bearing capacity decreases dramatically, and the thickness available for plastic deformation is severely reduced. This leads to a significant drop in the tensile strength and elongation at break of the current collector, making it difficult for current collectors of conventional strength to meet the needs of rechargeable batteries. Thinning of current collectors of ordinary strength can easily cause fatigue fracture in the later stages of battery cycling, potentially leading to thermal runaway and safety accidents. Therefore, it is necessary to effectively improve the tensile strength and plasticity (elongation at break) of the current collector while simultaneously reducing its thickness.
[0086] Existing metal strengthening techniques often utilize ordinary incoherent grain boundaries or phase boundaries to impede dislocation movement and thus improve strength. While introducing a large number of incoherent grain boundaries significantly increases strength, the increasing number of these "obstacles" severely hinders or even completely suppresses lattice dislocation movement, making it impossible to coordinate plastic deformation and consequently causing the material to become brittle. This means that strengthening the mechanical properties of metallic materials often comes at the cost of sacrificing plasticity, and materials with excellent plasticity often have very low strength.
[0087] Based on this, this application provides a current collector comprising a copper foil, wherein the average grain size of the grains in the copper foil is 50nm-400nm, and the proportion of nanotwins in the total number of grains in the copper foil is greater than or equal to 60%.
[0088] In this paper, the term "twin" refers to two crystals (or two parts of a single crystal) that are mirror-symmetric along a common crystal plane (i.e., a specific orientation relationship). These two crystals are called "twins," and this common crystal plane is called the twin plane. Nanotwins refer to twins with dimensions less than 1000 nanometers in all dimensions.
[0089] The average grain size in copper foil can be tested using methods known in the art. As an example, the cross-section of the copper foil is measured using electron backscatter diffraction (EBSD) and scanning electron microscopy. A range of copper foil not less than 5mm × 5mm and not more than 8mm × 8mm is selected to obtain the inverse pole figure distribution of the copper foil. The average diameter of the equivalent circle of the grains is taken as the grain size, and the grain size within this range is statistically analyzed to create a quantity distribution map. Figure 1 As shown, a skewed distribution is used for fitting, and the length corresponding to the peak value is taken as the average grain size.
[0090] In some embodiments, the average grain size of the copper foil can be selected as 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm or any value range between the two.
[0091] In some embodiments, the average grain size of the copper foil is 50 nm to 300 nm.
[0092] Copper foil with an average particle size within the above range can further improve its mechanical strength while maintaining the high plasticity of copper foil, thus meeting the application requirements of the new generation of high energy density secondary batteries.
[0093] In some embodiments, based on the total number of grains in the copper foil, the number of grains with a diameter less than 200 nm accounts for 20%-40%, and the number of grains with a diameter between 200 nm and 500 nm accounts for 50%-80%.
[0094] In some embodiments, based on the total number of grains in the copper foil, the percentage of grains with a diameter less than 200 nm can be selected as 20%, 24%, 28%, 32%, 36%, 40%, or any value between the two.
[0095] In some embodiments, based on the total number of grains in the copper foil, the percentage of grains with a diameter between 200 nm and 500 nm can be selected as 50%, 55%, 60%, 65%, 70%, 75%, 80%, or any value between the two.
[0096] In some embodiments, based on the total number of grains in the copper foil, the proportion of grains with a diameter greater than 500 nm is less than or equal to 5%, and can be selected as less than or equal to 2%.
[0097] In some embodiments, based on the total number of grains in the copper foil, the percentage of grains with a diameter greater than 500 nm can be selected as 0.5%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any value range between the two.
[0098] The copper foil provided in this application has a small average grain size and a skewed grain size distribution. The number of grains with a grain size greater than 500 nm is very small. The fine grains reduce the occurrence of concentrated stress during the deformation of the copper foil and are more conducive to grain cooperative slip. Therefore, the strength of the copper foil can be improved while the elongation at break can be increased.
[0099] In this application, the grain size ratio of nanotwins can be tested using methods known in the art. As an example, electron backscatter diffraction (EBSD) combined with scanning electron microscopy is used to observe the cross-section of the copper foil. A copper foil area of not less than 5mm × 5mm and not more than 8mm × 8mm is selected to obtain the inverse pole figure distribution of the copper foil, where different colors represent different grain orientations. Figure 2For example, the red lines inside the grains represent twin boundaries, indicating the presence of twinned structures. The size and number of twins can be counted using the analysis software accompanying the electron backscatter diffractometer, thereby calculating the proportion of nanotwin grains. As an example, the grain characteristics were analyzed using an Oxford C-Nano+ electron backscatter diffractometer and its accompanying software.
[0100] In some embodiments, the percentage of nanotwin grains can be selected as 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, or any value range between the two, based on the total number of grains in the copper foil.
[0101] Twin structures are an effective means of improving the strength and ductility of metals. Twin boundaries are coherent interfaces with orderly atomic arrangement, which can increase material strength by enhancing the resistance to dislocation movement while maintaining dislocation mobility, thus strengthening the material while preserving its ductility. However, copper foils reinforced by twins in existing technologies often introduce micron-sized twins during the fabrication process, hindering further improvements in copper foil strength. The copper foil provided in this application has a high proportion of nanotwins, significantly improving both the ductility and strength of the copper foil. The small grain size further increases the interface structure, raising the external stress required for dislocations to pass through grain boundaries, thereby achieving material strengthening. The high proportion of nanotwins and the small grain size work together to improve the mechanical strength of the copper foil while maintaining its high ductility, providing a material basis for further improvements in battery energy density and safety.
[0102] In this document, the term "equiaxed grain or equiaxed-like grain" refers to a grain whose major axis is equal to or very close to its minor axis. In some embodiments, the ratio a1 of the major axis to the minor axis of an equiaxed grain or equiaxed-like grain satisfies: 1 ≤ a1 < 2.
[0103] In some embodiments, based on the total number of grains in the copper foil, the proportion of equiaxed grains or quasi-equiaxed grains is greater than or equal to 80%, and can be selected as greater than or equal to 90%. The ratio a1 of the major axis to the minor axis of the equiaxed grains or quasi-equiaxed grains satisfies: 1≤a1<2.
[0104] In this application, the proportion of equiaxed grains or equiaxed-like grains can be tested using methods known in the art. As an example, electron backscatter diffraction (EBSD) combined with scanning electron microscopy is used to observe the cross-section of the copper foil. A copper foil range of not less than 5mm × 5mm and not more than 8mm × 8mm is selected to obtain the inverse pole figure distribution of the copper foil. The proportion of equiaxed grains or equiaxed-like grains is statistically analyzed using analysis software.
[0105] A large number of equiaxed grains or quasi-equiaxed grains are beneficial for achieving fine and uniform grains in copper foil. Furthermore, the properties of equiaxed grains or quasi-equiaxed grains are the same or similar in all directions, which is beneficial for comprehensively improving the strength and plasticity of copper foil.
[0106] In some embodiments, based on the total number of grains in the copper foil, the percentage of equiaxed grains or quasi-equiaxed grains is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, or any value between the two.
[0107] In some embodiments, based on the total number of grains in the copper foil, the proportion of columnar grains is less than 10%, and the ratio a2 of the major axis to the minor axis of the columnar grains satisfies: a2>2.
[0108] The formation of columnar grains easily leads to anisotropy in the mechanical properties of copper foil. Reducing the proportion of columnar grains is beneficial to improving the mechanical strength and plasticity of copper foil and reducing the probability of stress concentration points.
[0109] In some embodiments, the long axis of the columnar grains is oriented in the thickness direction of the copper foil.
[0110] In some embodiments, the diffraction intensity of the (111) texture in the copper foil accounts for more than or equal to 60% of the total diffraction intensity of the (111) texture, (200) texture, (220) texture, (311) texture and (222) texture in the copper foil, and may be selected as 60%-85%.
[0111] In this paper, the term "texture" refers to the orderly arrangement of grains in a polycrystalline material along certain directions during crystal formation, exhibiting more or less statistical non-uniform distribution, that is, clustering and arranging in certain directions, thus significantly increasing the probability of orientation in these directions, also known as preferred orientation or preferred orientation.
[0112] In this application, the diffraction intensity of the crystal planes of the texture in the copper foil can be tested using methods known in the art. As an example, an X-ray diffractometer is used to test the copper foil, with reference to standard copper powder (PDF No. 04). The X-ray spectrum of 0836) is used as follows: the peak area of the diffraction peak located at 40º-45º is used as the crystal plane diffraction intensity of (111) texture; the peak area of the diffraction peak located at 47º-52º is used as the crystal plane diffraction intensity of (200) texture; the peak area of the diffraction peak located at 70º-75º is used as the crystal plane diffraction intensity of (220) texture; the peak area of the diffraction peak located at 85º-95º is used as the crystal plane diffraction intensity of (311) texture; and the peak area of the diffraction peak located at 103º-107º is used as the crystal plane diffraction intensity of (222) texture.
[0113] In some embodiments, the ratio of the crystal plane diffraction intensity of the (111) texture in the copper foil to the sum of the crystal plane diffraction intensities of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil can be selected as 60%, 65%, 70%, 75%, 80%, 85%, or any value range between the two.
[0114] For pure copper materials, common textures include (111), (200), (220), (311), and (222). According to crystallographic properties, the (111) crystal plane has a high atomic density and high mechanical strength, which can improve the twinning strengthening effect. A high proportion of (111) texture in copper foil is beneficial to improving the mechanical strengthening and shaping enhancement effect of copper foil.
[0115] In some embodiments, the copper foil has a first surface and a second surface opposite to each other, the thickness of the copper foil is denoted as H, the region from the first surface of the copper foil to a thickness range of 0.2H-0.5H is denoted as the first region of the copper foil, and the region from the second surface of the copper foil to a thickness range of 0.2H-0.5H is denoted as the second region of the copper foil, wherein the absolute value of the difference between the average grain size of the grains in the first region and the average grain size of the grains in the second region is less than or equal to 150 nm.
[0116] In some embodiments, the absolute value of the difference between the average grain size of the grains in the first region and the average grain size of the grains in the second region is 1 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 150 nm, or any value between the two.
[0117] The grain size and structure of the copper foil are highly uniform along the thickness direction, indicating that uniform deposition was achieved at different time points. The electroplating solution did not undergo significant polarization during the deposition process, which provides a basis for maintaining high strength and high ductility while having an ultra-thin thickness.
[0118] In some embodiments, the number of nanotwins accounts for 65% to 90% of the total number of grains in the copper foil.
[0119] In some implementations, the maximum surface roughness of the copper foil is less than or equal to 3 μm.
[0120] The maximum surface roughness of copper foil reflects its surface uniformity and smoothness. The maximum surface roughness of copper foil can be tested using methods known in the art, such as a stylus roughness tester. The copper foil surface is wiped with alcohol, placed stably on a horizontal surface, and the stylus roughness tester is placed on the surface, allowing the probe to contact the surface and gently slide along it. The roughness is then measured by the instrument reading. This test is performed five times at different locations on the copper foil, and the maximum reading is taken as the maximum surface roughness.
[0121] In some embodiments, the maximum surface roughness of the copper foil can be selected as 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or any value range between the two.
[0122] Copper foil with a maximum surface roughness of less than or equal to 3μm has a smooth and uniform surface, which makes it less likely to form stress concentration points during cyclic stress, thus improving the mechanical strength and plasticity of the copper foil.
[0123] In some embodiments, the thickness H of the copper foil satisfies: 3μm≤H≤15μm, and can be optionally 3μm≤H≤8μm.
[0124] In some embodiments, the thickness H of the copper foil can be selected as 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm or any value range between the two.
[0125] In this application, the thickness of the copper foil can be tested using methods known in the art. For example, a 20×15cm² sample is cut, and the cut strip is weighed on an electronic balance to obtain the weight of the strip. Then, based on the density ρ of the copper foil being 8.96 g / cm³, the thickness is determined. 3 The volume of the spline is calculated. Since the length and width of the spline are known, the thickness of the spline can be calculated from this.
[0126] The copper foil has a low thickness, which enables effective weight reduction of the battery and is conducive to further improving the battery's energy density.
[0127] In some embodiments, under test conditions of room temperature, sample thickness of 6±0.2μm, and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is greater than or equal to 600MPa and the elongation at break of the copper foil is greater than or equal to 4%; optionally, the tensile strength of the copper foil is 700MPa-1500MPa, more preferably 800MPa-1000MPa; and the elongation at break of the copper foil is 4.5%-10%, more preferably 5%-8%.
[0128] In this article, the term "room temperature" refers to 20±10℃.
[0129] In this paper, the term "tensile strength" refers to the maximum load-bearing capacity of a specimen when it is subjected to continuous loading until it breaks.
[0130] In this paper, the term "elongation at break" refers to the ratio of the length change of a material from its original length to its original length after plastic deformation under stress. It is usually expressed as a percentage and is an important parameter for measuring the ability of a material to deform under stress during tension.
[0131] In this application, the tensile strength and elongation at break of the copper foil can be tested using methods known in the art, such as according to GB / T 5230-1995 "Electrolytic Copper Foil" standard. As an example, at least four specimens with a length of 200±0.5 mm, a width of 15±0.25 mm, and a thickness of 6±0.2 μm are cut. The specimens are continuously loaded at a tensile speed of 50±0.5 mm / min at room temperature until breakage. The tensile strength of the specimen is obtained by dividing the maximum load by the cross-sectional area of the specimen. The cross-sectional area of the specimen can be calculated by dividing the specimen mass by the product of the specimen length and density. The density of the copper foil specimen can be taken as 8.9 g / cm³. 3 .
[0132] In some embodiments, under test conditions of room temperature, sample thickness of 6 μm ± 0.2 μm, and tensile speed of 50 ± 0.5 mm / min, the tensile strength of the copper foil can be selected as 600 MPa, 700 MPa, 800 MPa, 900 MPa, 1000 MPa, 1100 MPa, 1200 MPa, 1300 MPa, 1400 MPa, 1500 MPa, or any value range between the two; the elongation at break of the copper foil can be selected as 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, or any value range between the two.
[0133] The aforementioned copper foil possesses both high strength and high plasticity, which can meet the requirements of high energy density batteries, improving battery safety while increasing battery energy density.
[0134] This application also provides a method for preparing copper foil, which uses electroplating to prepare copper foil. The electroplating method specifically includes periodically applying current to an electroplating solution to reduce and deposit copper ions in the electroplating solution to form copper foil. The average grain size of the copper foil is 50nm-400nm, and based on the total number of grains in the copper foil, the proportion of nanotwins is greater than or equal to 60%, and optionally greater than or equal to 65%.
[0135] In this article, the term "electroplating" refers to a method that uses the principle of electrolysis to deposit metal or alloy onto the surface of a workpiece to form a metal layer.
[0136] In some implementations, the current is a pulsed current, which includes one or more of square wave pulsed current, sine wave pulsed current, triangular wave pulsed current, and sawtooth wave pulsed current.
[0137] In some implementations, the pulse current includes a square wave pulse current.
[0138] In this paper, the term "pulse current" refers to a current or voltage pulse that repeats periodically.
[0139] Applying a pulsed current to the electroplating solution allows for control over the nucleation of reduced copper ions and grain growth by switching the current on and off. This suppresses grain growth, resulting in uniform nanocrystals and improving the tensile strength and elongation at break of the copper foil. Compared to the commonly used direct current deposition technology, pulsed current deposition can achieve a higher peak current density, which is beneficial for the extensive nucleation of copper foil, thereby increasing its density and reducing its grain size to improve its mechanical strength.
[0140] In some embodiments, the electroplating solution includes copper ions and chloride ions.
[0141] In some embodiments, the concentration of copper ions in the electroplating solution is 30 g / L-100 g / L, and can be selected as 45 g / L-75 g / L.
[0142] In some embodiments, the concentration of copper ions in the electroplating solution is 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, or any range between the two.
[0143] The results show that a combination of low copper ion concentration and high additive concentration is more beneficial for comprehensively improving the strength and elongation at break of copper foil than a combination of high copper ion concentration and low additive concentration. Furthermore, a low copper ion concentration helps control grain growth and deposition rates, which is conducive to preparing small-sized grains and improving the mechanical strength of the copper foil.
[0144] In some implementations, the concentration of chloride ions is 10 mg / L to 80 mg / L.
[0145] In some embodiments, the concentration of chloride ions is 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, or any range between the two.
[0146] In some embodiments, the electroplating solution further includes additives, which include one or more of leveling agents, wetting agents, and brighteners.
[0147] In this article, the term "leveling agent" refers to a substance added to the electroplating solution that can improve the smoothness of the plating layer.
[0148] In this article, the term "wetting agent" refers to a substance used to reduce the interfacial tension between the electroplating solution and the electrode, thereby enabling the coating to adhere better to the substrate.
[0149] In this article, the term "brightener" refers to a substance that improves the smoothness of the coating and reduces surface roughness.
[0150] Leveling agents can adhere to the tips of copper foils with fast deposition rates, inhibiting grain growth, balancing the growth rates of pits and tips, and improving the flatness of the copper foil. Wetting agents can improve the wettability of the plating solution and the substrate. The wettability of the plating solution on the cathode is sufficient to enable rapid electrodeposition with high current, increasing the nucleation rate of the copper foil and reducing the average grain size in the copper foil. Brighteners can make the grain size of the copper foil finer and reduce the surface roughness of the copper foil, improving the surface smoothness.
[0151] In some embodiments, the additives include leveling agents, wetting agents, and brightening agents.
[0152] The research results show that the simultaneous addition of multiple additives can produce a synergistic effect, effectively improving the strength and plasticity of copper foil.
[0153] In some embodiments, the leveling agent includes one or more of gelatin and Janus Green; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; and the brightening agent includes one or more of sodium dithiodipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and thiourea.
[0154] In some embodiments, the wetting agent includes hydroxyethyl cellulose and polyethylene glycol.
[0155] The results show that adding two different wetting agents simultaneously can more effectively improve the mechanical strength of copper foil compared to adding a single type of wetting agent. Although the mechanism is not yet clear, it is speculated that it may be related to the competitive adsorption of the two different types of additives, which is beneficial to improving the uniformity of grains during the deposition process, reducing the difference in grain size in the thickness direction, and improving the uniformity of copper foil.
[0156] In some embodiments, the concentration of the leveling agent in the electroplating solution is 20 mg / L-300 mg / L, and optionally 50 mg / L-150 mg / L.
[0157] In some embodiments, the concentration of the leveling agent in the electroplating solution is 20 mg / L, 50 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 250 mg / L, 300 mg / L, or any value range between the two.
[0158] In some embodiments, the concentration of the wetting agent in the electroplating solution is 10 mg / L-200 mg / L, and optionally 30 mg / L-100 mg / L.
[0159] In some embodiments, the concentration of the wetting agent in the electroplating solution is 10 mg / L, 30 mg / L, 50 mg / L, 80 mg / L, 100 mg / L, 130 mg / L, 150 mg / L, 180 mg / L, 200 mg / L, or any range between the two.
[0160] In some embodiments, the concentration of the brightener in the electroplating solution is 10 mg / L-200 mg / L.
[0161] In some embodiments, the concentration of the brightener in the electroplating solution is 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L, 110 mg / L, 120 mg / L, 130 mg / L, 140 mg / L, 150 mg / L, 160 mg / L, 170 mg / L, 180 mg / L, 190 mg / L, 200 mg / L, or any range between the two.
[0162] In some implementations, the pH of the electroplating solution is 2.5-4.4.
[0163] In some embodiments, the pH of the electroplating solution is 2.5, 2.7, 2.9, 3.1, 3.3, 3.5, 3.7, 3.9, 4.1, 4.4, or any value between two of these.
[0164] In some embodiments, the mass concentration ratio of the copper ions to the leveling agent is 500:1-4500:1; and / or, the mass concentration ratio of the copper ions to the brightener is 300:1-6000:1.
[0165] In some embodiments, the mass concentration ratio of the copper ions to the leveling agent can be selected as 500:1, 1000:1, 1500:1, 2000:1, 2500:1, 3000:1, 3500:1, 4000:1, 4500:1 or any range between the two.
[0166] In some embodiments, the mass concentration ratio of the copper ions to the brightener can be selected as 300:1, 1000:1, 2000:1, 3000:1, 4000:1, 5000:1, 6000:1 or any range between the two.
[0167] In some embodiments, the electroplating solution includes gelatin at a concentration of 20 mg / L-150 mg / L, polyethylene glycol at a concentration of 15 mg / L-100 mg / L, hydroxyethyl cellulose at a concentration of 10 mg / L-80 mg / L, sodium polydisulfide dipropane sulfonate at a concentration of 15 mg / L-150 mg / L, copper ions at a concentration of 45 g / L-90 g / L, and chloride ions at a concentration of 10 mg / L-80 mg / L.
[0168] In some embodiments, the peak current density of the pulse current is I, in A / dm². 2 The duty cycle of the pulse current is s, and the peak current density I satisfies the condition 2A / dm². 2 ≤I×s≤18A / dm 2 .
[0169] In this paper, the term "current duty cycle of a pulse current" refers to the proportion of the current conduction time of a pulse current in the entire pulse cycle.
[0170] In some implementations, the product of the peak current density I and the duty cycle s, I×s, is 2 A / dm. 2 4A / dm 2 6A / dm 2 8A / dm 2 10A / dm 2 12A / dm 2 14A / dm 2 16A / dm 2 18A / dm 2 Or the range of values between any two.
[0171] The product of peak current density I and duty cycle s corresponds to the average current density within the pulse period. Pulsed current deposition allows for an average current density higher than the maximum achievable current density with direct current deposition. Excessive direct current deposition density can lead to hydrogen evolution and concentration polarization in the plating solution, reducing the uniformity of the copper foil during electrodeposition. The product of peak current density I and duty cycle s within the aforementioned range allows for a dynamic balance between the consumption and replenishment of copper ions in the plating solution by controlling the on / off state of the current. This reduces the concentration difference between the copper ion deposition site and other parts of the plating solution, preventing significant concentration polarization and improving the uniformity of grain size in the thickness direction of the prepared copper foil. Furthermore, the product of peak current density I and duty cycle s within the aforementioned range can control grain nucleation and growth rates, enabling the preparation of small-diameter grains and improving the mechanical strength of the copper foil.
[0172] In some embodiments, the peak current density I of the pulse current satisfies: 3.3A / dm²≤I≤333A / dm².
[0173] In some embodiments, the peak current density I of the pulse current is 3.3 A / dm² or 8.35 A / dm². 2 10A / dm², 100A / dm², 150A / dm², 167A / dm², 180A / dm², 200A / dm², 300A / dm², 333A / dm², or any value range between the two.
[0174] In some implementations, the duty cycle s of the pulse current is 2% to 50%.
[0175] In some embodiments, the duty cycle s of the pulse current is 2%, 3.30%, 5%, 10%, 20%, 30%, 40%, 50%, or any value between the two.
[0176] In some implementations, the pulse width of the pulse current is 1ms to 50ms.
[0177] In this paper, the term "pulse width" refers to the duration of the current within a pulse period.
[0178] In some implementations, the pulse width of the pulse current is 1ms, 5ms, 10ms, 15ms, 20ms, 25ms, 30ms, 35ms, 40ms, 45ms, 50ms, or any value between the two.
[0179] In some embodiments, the distance between the cathode electrode and the anode electrode is 15mm to 20mm.
[0180] In some embodiments, the distance between the cathode electrode and the anode electrode is 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, or any value between the two.
[0181] In some embodiments, the deposition temperature is 45°C-60°C.
[0182] In some implementations, the deposition temperature can be selected as 45°C, 50°C, 55°C, 60°C, or any value between the two.
[0183] In some embodiments, the cathode electrode is a titanium roller or a titanium plate.
[0184] In some embodiments, the anode electrode is a titanium substrate plate.
[0185] In some implementations, the deposition time is greater than or equal to 80 seconds.
[0186] In some implementations, the deposition time can be selected as 80s, 100s, 200s, 220s, 240s, 280s, 300s, 400s, 500s, 800s, 1000s or any value range between the two.
[0187] In some embodiments, the electroplating method specifically includes periodically applying a pulsed current to the electroplating solution, causing copper ions in the electroplating solution to be reduced and deposited; wherein the peak current density I of the pulsed current satisfies 100A / dm²≤I≤180A / dm², the duty cycle s of the pulsed current satisfies 2%≤s≤10%, and the deposition time is 80s-250s.
[0188] In some embodiments, the preparation method is a continuous production method.
[0189] In some embodiments, the preparation method is a roller deposition method. Its working principle is that the cathode roller is connected to the negative terminal of the power supply, and the anode tank is connected to the positive terminal. When the electroplating solution containing copper ions enters the anode tank, an electric field is formed between the positive and negative electrodes. Under the action of the electric field, copper ions migrate to the surface of the cathode roller and are deposited. The deposited copper foil is peeled off from the cathode roller and wound onto another roller. The electroplating solution is continuously added and circulated, and copper ions are continuously deposited on the cathode roller under the action of the electric field, continuously peeled off, and wound onto the winding shaft. This preparation method enables large-scale continuous production of copper foil, providing possibilities for industrial applications.
[0190] This application also provides a copper foil, which includes the same features as the copper foil in the aforementioned current collector, and will not be repeated here.
[0191] In any embodiment, the copper foil is prepared by the preparation method described in any of the above embodiments.
[0192] In some embodiments, the maximum width of the copper foil is greater than or equal to 1.5 meters, and / or the maximum length of the copper foil is greater than or equal to 10,000 meters.
[0193] In some embodiments, the maximum width of the copper foil is 1.5 meters, 2 meters, 2.5 meters, 3 meters, 3.5 meters, 4 meters, 6 meters, 8 meters, 10 meters, or any value between two of these.
[0194] In some embodiments, the maximum length of the copper foil is 10,000 meters, 15,000 meters, 20,000 meters, 25,000 meters, 30,000 meters, 60,000 meters, 100,000 meters, or any value between two of these.
[0195] The copper foil provided in this application embodiment can be manufactured in large sizes and has the prospect of industrial application.
[0196] Polaroid This application also provides an electrode, which includes a current collector in any embodiment.
[0197] In some implementations, the electrode is a negative electrode and the current collector is a negative current collector.
[0198] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector. For example, the negative current collector has two surfaces opposite each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative current collector.
[0199] In some embodiments, the negative electrode film layer comprises a negative electrode active material. In some embodiments, the negative electrode active material includes, but is not limited to, one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy materials. The tin-based material may include one or more of elemental tin, tin oxide, and tin alloy materials.
[0200] In some embodiments, the electrode is a negative electrode, which includes a current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector. The negative electrode film layer contains a negative electrode active material, which contains a silicon-based material. The tensile elongation at break of the negative electrode at room temperature is greater than or equal to 2%, and can be selected as 3%-5%.
[0201] In this article, the term "room temperature" refers to 20±10℃.
[0202] In this paper, the term "tensile elongation at break" refers to the ratio of the length change of a material from deformation to fracture after being subjected to stress to its original length. It is usually expressed as a percentage and is an important parameter for measuring the ability of a material to deform under stress during tension.
[0203] The tensile elongation at break of the negative electrode sheet can be tested using methods known in the art. As an example, at least four samples with a length of 200 ± 0.5 mm and a width of 15 ± 0.25 mm are cut from the negative electrode sheet. Using pneumatic clamps with an air pressure of 0.2 MPa, the electrode sheet is passed through the upper and lower clamps. The air valve is activated to clamp the upper clamp first, maintaining a weak connection (i.e., keeping the sample in a naturally bent state, without applying external force), and then clamping the lower clamp. A tensile load is continuously applied to the sample at a tensile speed of 2 mm / min until it breaks, with a gauge length of 50 mm. The tensile elongation at break of the negative electrode sheet is calculated by dividing the elongation between the gauge lengths at the point of tensile fracture by the length between the gauge lengths before tensile fracture.
[0204] In some embodiments, the tensile elongation at break of the negative electrode at room temperature can be selected as 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any value range between the two.
[0205] In some implementations, the thickness of the negative electrode sheet is 100-150 μm, which is measured directly using a micrometer.
[0206] The negative electrode of this secondary battery has a high tensile elongation at break, which provides sufficient room for expansion during the later stages of the secondary battery cycle. This allows the secondary battery with silicon-based materials to simultaneously improve safety performance and cycle life while maintaining high energy density.
[0207] In some embodiments, the compacted density of the negative electrode sheet is greater than or equal to 1.5 g / cm³. 3 Furthermore, the cold-pressed elongation rate of the negative electrode sheet is less than or equal to 0.1%, and can be selected as 0.06%-0.1%.
[0208] In this application, the compaction density of the negative electrode sheet has a meaning known in the art and can be tested using methods known in the art. The compaction density of the negative electrode sheet = the areal density of the negative electrode film layer / the thickness of the negative electrode film layer. The thickness of the negative electrode film layer has a meaning known in the art and can be tested using methods known in the art, such as using a micrometer (e.g., a Mitutoyo 293-100 model with an accuracy of 0.1 μm). The areal density of the negative electrode film layer can be tested using methods known in the art. For example, a cold-pressed negative electrode sheet or a negative electrode sheet obtained after disassembling a battery (if it is a double-coated negative electrode sheet, the negative electrode film layer on one side can be wiped off first) can be punched into a small circular piece with an area of S1, weighed, and recorded as M1. Then, the negative electrode film layer of the weighed negative electrode sheet is wiped off, and the weight of the negative current collector is weighed and recorded as M0. The areal density of the negative electrode sheet = (M1 - M0) / S1.
[0209] In some embodiments, the compaction density of the negative electrode sheet can be selected as 1.5 g / cm³. 3 1.55g / cm 3 1.6g / cm 3 1.65g / cm 3 1.7g / cm 3 1.75g / cm 3 1.8g / cm 3 1.85g / cm 3 1.9g / cm 3 1.95g / cm 3 2.0g / cm 3 Or the range of values between any two.
[0210] The cold-press elongation of the negative electrode sheet can be tested using methods known in the art. As an example, two points are taken on the surface of the negative electrode sheet before cold pressing, along the direction perpendicular to the cold pressing roller (MD), and the distance L1 between them is measured; the distance L2 between the two points is measured on the negative electrode sheet after cold pressing, and (L2-L1) / L1 is taken as the cold-press elongation of the negative electrode sheet. Measurements are taken at least five different sites, and the average value is taken as the cold-press elongation of the negative electrode sheet. It should be understood that the cold-press elongation of the negative electrode sheet can also be obtained by characterizing a disassembled secondary battery. As an example, the negative electrode sheet is obtained by disassembling a secondary battery, and the difference between the current collector elongation at break in the negative electrode film-covered area and the current collector elongation at break in the empty foil area is tested; this difference can also be used to characterize the cold-press elongation of the negative electrode sheet.
[0211] In some implementations, the cold-pressed elongation of the negative electrode sheet can be selected as 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, or any value range between the two.
[0212] The negative electrode of this secondary battery achieves high compaction density while exhibiting low elongation during cold pressing. This allows for more space for expansion during battery cycling, improving battery safety and cycle life. Furthermore, the low elongation during cold pressing reduces the risk of wrinkling at the tabs of the negative electrode during the cold pressing process, potentially eliminating the need for the pre-stretching process currently used to reduce wrinkling during cold pressing and improving production efficiency.
[0213] In some embodiments, the compaction density of the negative electrode sheet is 1.5 g / cm³. 3 -2.0g / cm 3 .
[0214] Silicon-based materials have higher hardness and relatively poor slipability compared to carbon-based active materials commonly used in anodes, thus requiring greater cold-pressing pressure to achieve the same compaction density. This silicon-containing anode in the secondary battery exhibits high resistance to stretching and can achieve a high compaction density, thereby improving battery safety and lifespan while further increasing the energy density of the secondary battery.
[0215] In some embodiments, the silicon-based material has a mass content of 5%-100% based on the total mass of the negative electrode film.
[0216] In some embodiments, based on the total mass of the negative electrode film, the mass content of the silicon-based material can be selected as 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, or any value range between the two.
[0217] In some embodiments, the silicon-based material has a mass content of 10%-60% based on the total mass of the negative electrode film.
[0218] Silicon-based materials within the above content range enable secondary batteries to possess good energy density, safety, and cycle stability.
[0219] In some embodiments, the thickness of the current collector is 2-10 μm.
[0220] In some embodiments, the thickness of the current collector can be selected as 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any value range between the two. The thickness of the current collector can be measured by any method known in the art. As an example, the thickness of the current collector can be measured by a thickness gauge. Alternatively, the current collector can be punched into small discs, weighed, and the areal density of the sample can be obtained by dividing the sample mass by the sample surface area. The thickness of the current collector can then be calculated by dividing the areal density of the sample by the density of the current collector material (e.g., if the current collector is copper foil, the density of the current collector is 8.9 g / cm³). 3 The density of the current collector material can be characterized using a composition analyzer.
[0221] In some embodiments, the negative electrode film layer may optionally include a negative electrode conductive agent. This application does not impose any particular limitation on the type of negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0222] In some embodiments, the negative electrode film layer may optionally include a negative electrode binder. This application does not impose any particular limitation on the type of negative electrode binder. As an example, the negative electrode binder may include one or more of the following: styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0223] In some embodiments, the negative electrode film may optionally include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc.
[0224] The negative electrode film layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional additives in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited to these.
[0225] The negative electrode sheet does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet of this application further includes a conductive undercoat layer (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode sheet of this application further includes a protective layer covering the surface of the negative electrode film layer.
[0226] Secondary batteries This application also provides a secondary battery, which can be in the form of a battery cell, a battery module, or a battery pack.
[0227] In some embodiments, the maximum expansion force of the secondary battery cell is greater than or equal to 1000 kgf.
[0228] In some embodiments, the maximum expansion force of the secondary battery cell is greater than or equal to 2500 kgf.
[0229] In some embodiments, the maximum expansion force of the secondary battery cell is greater than or equal to 4000 kgf.
[0230] Here, 1 kgf refers to the gravitational force exerted on a 1-kilogram object at sea level at 45 degrees north latitude. 1 kgf is approximately 9.8 Newtons. The expansion force of the secondary battery cell is sensed by pressure sensors located in clamps on both sides of the large surface of the electrode of the secondary battery cell.
[0231] Current collectors in existing technologies are prone to fracture under the high expansion force of secondary batteries, leading to safety accidents and limiting further improvements in the electrochemical performance of secondary batteries. The current collector provided in this application has both excellent tensile strength and elongation at break, making it suitable for secondary batteries with high expansion force and beneficial for further improving the energy density of secondary batteries.
[0232] This application does not impose any particular limitation on the type of secondary battery; for example, the secondary battery can be a lithium-ion battery. Typically, a secondary battery includes a positive electrode, a negative electrode, and an electrolyte. During the charging and discharging process of the secondary battery, active ions repeatedly insert and extract between the positive and negative electrodes, and the electrolyte acts as a conductor for these active ions. This application does not impose any particular limitation on the type of electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of solid electrolytes and liquid electrolytes (i.e., electrolyte solutions). Secondary batteries using electrolyte solutions, and some secondary batteries using solid electrolytes, may also include a separator membrane disposed between the positive and negative electrodes to provide isolation.
[0233] [Positive electrode plate] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. For example, the positive current collector has two surfaces opposite each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0234] The positive electrode current collector can be a metal foil or a composite current collector. As an example of a metal foil, copper foil can be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0235] The positive electrode film typically comprises a positive electrode active material, an optional binder, and an optional conductive agent. The positive electrode film is typically formed by coating a positive electrode slurry onto the positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring until homogeneous. The solvent may be N-methylpyrrolidone (NMP), but is not limited to this. As an example, the binder used for the positive electrode film may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins. As an example, the conductive agent used for the positive electrode film includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0236] The positive electrode active material may be a positive electrode active material known in the art for use in secondary batteries.
[0237] When the secondary battery of this application is a lithium-ion battery, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, lithium phosphates, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, and their respective modified compounds. Examples of lithium phosphates may include, but are not limited to, lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composites, and their respective modified compounds.
[0238] In some embodiments, to further improve the energy density of secondary batteries, the positive electrode active material for lithium-ion batteries may include materials with the general formula Li. a Ni b Coc M d O e A f is one or more of lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from one or more of N, F, S and Cl.
[0239] In some embodiments, by way of example, the positive electrode active material for lithium-ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O2, LiFePO4 and LiMnPO4, one or more thereof.
[0240] In the present application, the modified compounds of the above positive electrode active materials may be those obtained by doping modification and / or surface coating modification of the positive electrode active materials.
[0241] [Electrolyte] In some embodiments, the electrolyte adopts an electrolytic solution, and the electrolytic solution includes an electrolyte salt and a solvent.
[0242] The type of the electrolyte salt is not particularly limited, and can be selected according to actual needs.
[0243] When the secondary battery of this application is a lithium-ion battery, as an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).
[0244] The type of solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl ethylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0245] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain performance characteristics of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high-temperature performance of the secondary battery, and additives that improve the low-temperature power performance of the secondary battery.
[0246] [Isolation membrane] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.
[0247] In some embodiments, the material of the separator may include one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.
[0248] In some embodiments, the positive electrode, the separator, and the negative electrode can be fabricated into an electrode assembly using a winding process or a stacking process.
[0249] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0250] In some embodiments, the outer packaging may be a hard shell, such as a hard plastic shell, aluminum shell, steel shell, etc. The outer packaging may also be a flexible package, such as a pouch. The material of the flexible package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0251] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. Figure 5 This is an example of a square-structured secondary battery 5.
[0252] In some embodiments, such as Figure 6 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. The positive electrode, negative electrode, and separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated in the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The secondary battery 5 may contain one or more electrode assemblies 52, which can be adjusted according to requirements.
[0253] The method for preparing the secondary battery described in this application is well known. In some embodiments, a positive electrode, a separator, a negative electrode, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode, separator, and negative electrode can be formed into an electrode assembly through a winding or stacking process. The electrode assembly is then placed in an outer packaging, dried, and injected with an electrolyte. After vacuum sealing, settling, formation, and shaping, a secondary battery is obtained.
[0254] In some embodiments of this application, the secondary battery according to this application can be assembled into a battery module. The number of secondary batteries contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0255] Figure 7 This is a schematic diagram of battery module 4 as an example. Figure 7 As shown, in battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.
[0256] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.
[0257] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0258] Figure 8 and Figure 9 This is a schematic diagram of battery pack 1 as an example. Figure 8 and Figure 9 As shown, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3. The upper body 2 covers the lower body 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0259] Electrical appliances This application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack described in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, mobile devices (e.g., mobile phones, tablets, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0260] The electrical device can be equipped with a secondary battery, battery module, or battery pack according to its usage requirements.
[0261] Figure 10 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.
[0262] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use rechargeable batteries as their power source.
[0263] Example The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0264] Example 1 (1) Preparation of copper foil Copper plates or wires with a purity of 99.9% or higher are dissolved in sulfuric acid solution to prepare a copper sulfate pentahydrate solution. This solution is used as the copper source. An electroplating solution is prepared at 60°C with additives and oxalic acid. The additives include gelatin, polyethylene glycol, hydroxyethyl cellulose, and sodium chloride. The pH of the electroplating solution is 3.5. The concentrations of each component are as follows: copper ions 45 g / L; gelatin 90 mg / L; polyethylene glycol 50 mg / L; hydroxyethyl cellulose 30 mg / L; chloride ions 80 mg / L; sodium polydithiopropane sulfonate 75 mg / L; and the remainder is deionized water.
[0265] A square-wave pulsed current waveform was used to periodically apply current to a polished cathode titanium roller. The titanium roller, with an area of 0.3 dm², was located in the electroplating bath and rotated at a speed of 2 m / min. The applied pulsed current had a current density of 167 A / dm², a duty cycle of 5%, and a pulse width of 1 ms. The cathode-anode distance was 20 mm, and the deposition temperature was 60 °C. The electroplating time was 224 s, and a copper foil with a thickness of 6 μm was deposited on the titanium roller.
[0266] (2) Battery preparation LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are dissolved in solvent N-methylpyrrolidone (NMP) at a weight ratio of 90:5:5. After thorough stirring and mixing, a positive electrode slurry is obtained. The positive electrode slurry is then uniformly coated onto the positive electrode current collector, and after drying, cold pressing, and slitting, a positive electrode sheet is obtained.
[0267] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water in a weight ratio of 90:4:4:2 and mixed evenly to prepare a negative electrode slurry. The negative electrode slurry is then coated evenly on the negative electrode current collector copper foil once or multiple times, dried to obtain a negative electrode film, and then cold-pressed and slit to obtain a negative electrode sheet.
[0268] In an argon-atmospheric glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), and ethyl methyl carbonate (EMC) were mixed uniformly at a mass ratio of 1:2:7. Then, 12.5 wt% LiPF6 lithium salt was dissolved in the organic solvent. Next, 2.0 wt% fluoroethylene carbonate, 0.5 wt% 1,3-propanesulfonate lactone, and 0.5 wt% succinic anhydride were added as additives to the above organic solvent, and the mixture was stirred until homogeneous to obtain the electrolyte.
[0269] Polypropylene film is used as the separator.
[0270] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The electrodes are then wound to obtain the electrode assembly. The electrode assembly is placed in the battery casing, dried, and then injected with electrolyte. After formation and settling processes, a lithium-ion battery is obtained.
[0271] Examples 2-8 The preparation methods of Examples 2-8 are basically the same as those of Example 1, except that the composition or concentration of the electrolyte or the parameters of pulse deposition are changed, as shown in Table 1.
[0272] Example 9 The preparation method of Example 9 is basically the same as that of Example 1, except that the ratio of the negative electrode sheet is changed. Specifically, the negative electrode active material silicon carbon (silicon content 20wt%-50wt%), artificial graphite, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water in a mass ratio of 10:86:1:1.5:1.5 and mixed evenly to prepare a negative electrode slurry. Then, the negative electrode slurry is uniformly coated on the negative electrode current collector copper foil once or multiple times, dried to obtain a negative electrode film, and then cold-pressed and slit to obtain the negative electrode sheet.
[0273] Example 10 Example 10 is basically the same as Example 9, except that the composition in the negative electrode film layer remains unchanged, and the ratio of each component in the negative electrode film layer is adjusted. Specifically, the ratio of the negative electrode film layer is 30:66:1:1.5:1.5 for the negative electrode active material silicon carbide, artificial graphite, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC).
[0274] Example 11 Example 11 is basically the same as Example 10, except that the compaction density of the negative electrode film layer is adjusted, as shown in Table 4.
[0275] Comparative Example 1 The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that the electrodeposition method is changed, and direct current is used for deposition with a deposition current density of 8.35 A / dm³. 2 The details are shown in Table 1.
[0276] Comparative Example 2 The preparation method of Comparative Example 2 is basically the same as that of Example 9, except that conventional copper foil in the prior art is used as the current collector with a thickness of 6 μm. Under the test conditions of room temperature, sample thickness of 6 ± 0.2 μm and tensile speed of 50 ± 0.5 mm / min, the tensile strength of the copper foil is 350 MPa and the elongation at break is 6.2%.
[0277] Comparative Example 3 The preparation method of Comparative Example 3 is basically the same as that of Comparative Example 2, except that a pre-stretching process is added before cold pressing during the preparation of the negative electrode sheet. Specifically, a pre-stretching roller with a tension of 400-700N is added before cold pressing to pre-stretch the blank area of the coated copper foil, thereby avoiding wrinkling problems caused by the film area stretching while the blank area does not stretch during cold pressing.
[0278] Table 1
[0279] Performance testing (1) Thickness test Take a 20×15cm² sample and calculate its thickness using the weighing method, as follows: Weigh the cut sample strip on an electronic balance to obtain its weight. Then, based on the density ρ of copper foil being 8.96g / cm³, calculate the thickness. 3 The volume of the spline is calculated. Since the length and width of the spline are known, the thickness of the spline can be calculated from this.
[0280] (2) Mechanical property testing According to GB / T 5230-1995 "Electrolytic Copper Foil", tensile specimens with a length L0 of 200 mm and a width of 15 mm were cut. The specimens were weighed on a balance and the mass was recorded as m. The tensile properties were tested using a universal testing machine at 25℃, with the tensile rate set to 50 mm / min.
[0281] Then the cross-sectional area S0 of the stretched spline = , where ρ is 8.96 g / cm³ 3 The unit of m is gram, and the unit of L0 is centimeter.
[0282] The specimen is continuously loaded until it breaks. The maximum load F is read from the force measuring plate or the tensile curve, and the tensile strength σ is calculated according to Formula I. b .
[0283]
[0284] Formula I The distance between the two lines after the specimen breaks is L1, which can be measured on the specimen or read from the tensile curve. L1 can be measured using the linear method or the displacement method, and the elongation at break δ can be calculated according to Formula II.
[0285]
[0286] Formula II (3) Grain characteristic test of copper foil Cross-sections of copper foil were observed using electron backscatter diffraction (EBSD) combined with scanning electron microscopy (SEM), with the Oxford C-Nano+ electron backscatter diffractometer used. Poleographic distribution maps were obtained, and the grain size of each grain was measured. The diameter of the equivalent circle of the grain was used as the grain size, and the grain size distribution was statistically analyzed. A skewed distribution was used for fitting, and the grain size corresponding to the peak value was taken as the average grain size in the copper foil. The number of twins was counted using inverse poleographic maps; different colors represent different grain orientations, and the red lines inside the grains are twin boundaries, indicating the presence of twinned structures. The proportion of nanotwins was determined using the analysis software accompanying the Oxford C-Nano+ electron backscatter diffractometer. The proportion of equiaxed or quasi-equiaxed grains was measured using a similar method.
[0287] (4) Maximum surface roughness test Wipe the surface of the copper foil with alcohol, place the copper foil stably on a horizontal surface, place the stylus-type roughness tester on the surface of the copper foil, make the stylus contact the surface of the copper foil, and gently slide the stylus along the surface. The roughness of the copper foil is obtained by reading the instrument. Test five times at different parts of the copper foil, and take the maximum value of the reading as the maximum surface roughness of the copper foil.
[0288] (5) State of Health (SOH) corresponding to crack failure At 25°C, the battery is charged at a constant current of 1C until the voltage reaches 3.8V, then charged at a constant voltage of 3.8V until the current is ≤0.05C. The battery is then discharged at a constant current of 1C until the voltage reaches 2.5V. This constitutes one charge-discharge cycle. This cycle is repeated. Computed tomography (CT) is then used to determine if cracks have formed inside the battery. If cracks are found, the battery that failed due to cracking during the cycle is disassembled. The negative electrode is removed, and samples are taken from areas without cracks. The elongation at break is measured using the method described above, and the state of equilibrium (SOH) value of the battery at this point is calculated through simulation.
[0289] (6) Cyclic simulation calculation: A fracture model was established based on finite element analysis, and the cell was modeled using hot-pressed rolled core (JR). Then, the electrode stretching curve was used as the mechanical parameter input. Finally, the expansion force data of the cell was used as the free rebound of the JR size as the input of the crack model. The electrode elongation rate of the cell under the expansion force was greater than the electrode fracture elongation rate as the criterion. The state of charge (SOH) corresponding to the electrode fracture during long-cycle operation was simulated and analyzed.
[0290] (7) Observation of the tab area after cold pressing: If wrinkles appear in the blank area of the electrode sheet, the electrode tab is considered wrinkled; if the blank area of the electrode sheet remains flat and without any abnormalities, the electrode tab is considered not wrinkled.
[0291] Test Results Table 2
[0292] Table 3
[0293] The test results of the examples and comparative examples are shown in Tables 1-3.
[0294] As can be seen from the comparison between the embodiments and the comparative examples, the average grain size of the copper foil provided in this application is 50nm-400nm, and based on the total number of grains in the copper foil, the number of twin grains accounts for no less than 60%. It has both excellent tensile strength and elongation at break, which can reduce the charge (SOH) value corresponding to battery crack failure, and help improve the safety and cycle life of the battery.
[0295] Figure 1 This is a schematic diagram of the grain size distribution of the copper foil in Example 1; Figure 2This is the inverse pole figure of the electron backscatter diffraction image of the copper foil in Example 1; Figure 3 This is a stretching curve of the copper foil from Example 1. Combined with... Figure 1 and Figure 2 As can be seen, the average grain size of the copper foil in Example 1 is 200 nm; the minimum grain size is about 10 nm; based on the total number of grains in the copper foil, the number of grains with a grain size below 200 nm accounts for 34%, the number of grains with a grain size between 200 and 500 nm accounts for about 65%, and the number of grains with a grain size greater than 500 nm accounts for no more than 2%; the maximum surface roughness of the copper foil is 0.12 μm. Figure 4 a is the X-ray diffraction pattern of the copper foil in Example 2; the diffraction intensity of the (111) texture in the copper foil is 80.06% of the sum of the diffraction intensities of the (111), (200), (220), (311), and (222) textures in the copper foil. Compared to Figure 4 b. In comparison to the copper foil in Example 1, the proportion of the diffraction intensity of the (111) texture in the copper foil to the total diffraction intensity of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil is significantly increased.
[0296] As shown in Table 3, when the additives in the electroplating solution contain a certain amount of leveling agent, wetting agent and brightener, the maximum roughness of the copper foil surface can be reduced, and the tensile strength and elongation at break of the copper foil can be further improved simultaneously.
[0297] As can be seen from the comparison of Examples 1, 2, and 8, compared with the electroplating solution containing high concentration of copper ions and low concentration of additives, the electroplating solution containing low concentration of copper ions and high concentration of additives can further improve the tensile strength and elongation at break of copper foil.
[0298] As can be seen from the comparison of Examples 1, 4, 6 and Example 5, the high peak current density and duty cycle product result in an increase in the average grain size of the copper foil and a decrease in its mechanical properties, but it is still better than Comparative Example 1.
[0299] Table 4
[0300] A comparison of Examples 9-11 with Comparative Example 3 shows that the secondary battery includes a negative electrode sheet, which includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The negative electrode film layer contains a negative electrode active material, which contains a silicon-based material. The tensile elongation at break of the negative electrode sheet at room temperature is greater than or equal to 2%, which can reduce the state of shock (SOH) corresponding to the breakage of the cell electrode sheet and improve the service life of the battery.
[0301] As can be seen from the comparison between Examples 9-11 and Comparative Example 2, when the current collector of this example is used in a secondary battery containing silicon-based materials, the tabs will not wrinkle after the pre-stretching process is eliminated during the preparation of the negative electrode sheet, thus optimizing the battery production process and improving production efficiency.
[0302] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A current collector, characterized in that, The current collector includes a copper foil, wherein the average grain size of the grains in the copper foil is 50nm-400nm, and based on the total number of grains in the copper foil, the proportion of nanotwins is greater than or equal to 60%; based on the total number of grains in the copper foil, the proportion of equiaxed grains or quasi-equiaxed grains is greater than or equal to 80%, and the ratio a1 of the major axis to the minor axis of the equiaxed grains or quasi-equiaxed grains satisfies: 1≤a1<2.
2. The current collector according to claim 1, characterized in that, The grains in the copper foil satisfy one or more of the following characteristics: (1) The average grain size of the copper foil is 50nm-300nm; (2) Based on the total number of grains in the copper foil, the proportion of grains with a diameter less than 200 nm is 20%-40%, and the proportion of grains with a diameter between 200 nm and 500 nm is 50%-80%; (3) Based on the total number of grains in the copper foil, the proportion of grains with a diameter greater than 500 nm is less than or equal to 5%; (4) Based on the total number of grains in the copper foil, the proportion of columnar grains is less than 10%, and the ratio of the length of the major axis to the minor axis of the columnar grains, a2, satisfies: a2 > 2; (5) The diffraction intensity of the (111) texture in the copper foil accounts for 60%-85% of the total diffraction intensity of the (111), (200), (220), (311), and (222) textures in the copper foil; (6) The copper foil has a first surface and a second surface, the thickness of the copper foil is denoted as H, the area from the first surface of the copper foil to the thickness range of 0.2H-0.5H is denoted as the first region of the copper foil, the area from the second surface of the copper foil to the thickness range of 0.2H-0.5H is denoted as the second region of the copper foil, and the absolute value of the difference between the average grain size of the grains in the first region and the average grain size of the grains in the second region is less than or equal to 150nm; (7) Based on the total number of grains in the copper foil, the number of grains in the nanotwins accounts for 65% to 90%.
3. The current collector according to claim 1 or 2, characterized in that, The copper foil satisfies one or more of the following characteristics: (1) The maximum surface roughness of the copper foil is less than or equal to 3 μm; (2) The thickness H of the copper foil satisfies: 3μm≤H≤15μm; (3) Under the test conditions of room temperature, sample thickness of 6±0.2μm and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is greater than or equal to 600MPa and the elongation at break of the copper foil is greater than or equal to 4%; (4) Under the test conditions of room temperature, sample thickness of 6±0.2μm and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is 700MPa-1500MPa; the elongation at break of the copper foil is 4.5%-10%.
4. An electrode sheet, characterized in that, The electrode comprises the current collector according to any one of claims 1 to 3.
5. The electrode sheet according to claim 4, characterized in that, The electrode is a negative electrode, and the tensile elongation at break of the negative electrode at room temperature is greater than or equal to 2%.
6. The electrode sheet according to claim 5, characterized in that, The tensile elongation at break of the negative electrode sheet at room temperature is 3%-5%.
7. A secondary battery, characterized in that, The electrode includes any one of claims 4 to 6.
8. The secondary battery according to claim 7, characterized in that, The maximum expansion force of the secondary battery is greater than or equal to 1000 kgf.
9. The secondary battery according to claim 7, characterized in that, The maximum expansion force of the secondary battery is greater than or equal to 2500 kgf.
10. The secondary battery according to claim 7, characterized in that, The maximum expansion force of the secondary battery is greater than or equal to 4000 kgf.
11. The secondary battery according to claim 7, characterized in that, The electrode is a negative electrode, which includes the current collector and a negative electrode film layer disposed on at least one side of the current collector. The negative electrode film layer contains a negative electrode active material, which contains a silicon-based material. The tensile elongation at break of the negative electrode at room temperature is greater than or equal to 2%.
12. The secondary battery according to claim 11, characterized in that, The tensile elongation at break of the negative electrode sheet at room temperature is 3%-5%.
13. The secondary battery according to claim 11, characterized in that, The compacted density of the negative electrode sheet is greater than or equal to 1.5 g / cm³. 3 Furthermore, the cold-pressed elongation of the negative electrode sheet is less than or equal to 0.1%.
14. The secondary battery according to claim 13, characterized in that, The cold-pressed elongation rate of the negative electrode sheet is 0.06%-0.1%.
15. The secondary battery according to claim 11, characterized in that, The compaction density of the negative electrode sheet is 1.5 g / cm³. 3 -2.0g / cm 3 .
16. The secondary battery according to any one of claims 11 to 15, characterized in that, Based on the total mass of the negative electrode film, the mass content of the silicon-based material is 5%-100%.
17. The secondary battery according to any one of claims 11 to 15, characterized in that, Based on the total mass of the negative electrode film, the mass content of the silicon-based material is 10%-60%.
18. The secondary battery according to any one of claims 11 to 15, characterized in that, Based on the total mass of the negative electrode film, the mass content of the silicon-based material is 10%-30%.
19. The secondary battery according to any one of claims 11 to 15, characterized in that, The thickness of the current collector is 2μm-10μm.
20. The secondary battery according to any one of claims 11 to 15, characterized in that, The thickness of the current collector is 2μm-7μm.
21. An electrical appliance, characterized in that, The secondary battery includes any one of claims 7 to 20.
22. A method for preparing copper foil, characterized in that, The copper foil is prepared by electroplating, specifically by periodically applying current to an electroplating solution to reduce and deposit copper ions in the solution to form the copper foil. The average grain size of the copper foil is 50nm-400nm, and based on the total number of grains in the copper foil, the proportion of nanotwins is greater than or equal to 60%; based on the total number of grains in the copper foil, the proportion of equiaxed grains or quasi-equiaxed grains is greater than or equal to 80%, and the ratio a1 of the major axis to the minor axis of the equiaxed grains or quasi-equiaxed grains satisfies: 1≤a1<2.
23. The preparation method according to claim 22, characterized in that, The current is a pulse current, which includes one or more of the following: square wave pulse current, sine wave pulse current, triangular wave pulse current, and sawtooth wave pulse current.
24. The preparation method according to claim 22, characterized in that, The electroplating solution includes additives, which include one or more of leveling agents, wetting agents, and brighteners.
25. The preparation method according to claim 24, characterized in that, The additives include leveling agents, wetting agents, and brighteners.
26. The preparation method according to claim 25, characterized in that, The electroplating solution meets one or more of the following conditions: (1) The concentration of the leveling agent in the electroplating solution is 20 mg / L-300 mg / L; (2) The concentration of the wetting agent in the electroplating solution is 10 mg / L-200 mg / L; (3) The concentration of the brightener in the electroplating solution is 10 mg / L-200 mg / L; (4) The concentration of copper ions in the electroplating solution is 30 g / L-100 g / L; (5) The concentration of chloride ions in the electroplating solution is 10 mg / L-80 mg / L; (6) The pH of the electroplating solution is 2.5-4.
4.
27. The preparation method according to claim 26, characterized in that, The electroplating solution meets one or more of the following conditions: (1) The concentration of the leveling agent in the electroplating solution is 50 mg / L-150 mg / L; (2) The concentration of the wetting agent in the electroplating solution is 30 mg / L-100 mg / L; (3) The concentration of copper ions in the electroplating solution is 45g / L-75g / L.
28. The preparation method according to claim 25, characterized in that, The leveling agent includes one or more of gelatin and Janus Green; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; and the brightening agent includes one or more of sodium dithiodipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and thiourea.
29. The preparation method according to claim 28, characterized in that, The wetting agent includes hydroxyethyl cellulose and polyethylene glycol.
30. The preparation method according to claim 26, characterized in that, The mass concentration ratio of copper ions to the leveling agent is 500:1-4500:1; and / or, The mass concentration ratio of copper ions to the brightener is 300:1-6000:
1.
31. The preparation method according to claim 26, characterized in that, The electroplating solution includes gelatin with a concentration of 20 mg / L-150 mg / L, polyethylene glycol with a concentration of 15 mg / L-100 mg / L, hydroxyethyl cellulose with a concentration of 10 mg / L-80 mg / L, sodium polydisulfide dipropane sulfonate with a concentration of 15 mg / L-150 mg / L, copper ions with a concentration of 45 g / L-90 g / L, and chloride ions with a concentration of 10 mg / L-80 mg / L.
32. The preparation method according to claim 23, characterized in that, The peak current density of the pulse current is I, with units of A / dm. 2 ; The duty cycle of the pulse current is s, and the peak current density I satisfies the condition 2A / dm. 2 ≤I×s≤18A / dm 2 .
33. The preparation method according to claim 32, characterized in that, The electroplating method satisfies one or more of the following conditions: (1) The peak current density I of the pulse current satisfies: 3.3A / dm²≤I≤333A / dm²; (2) The duty cycle s of the pulse current satisfies: 2% ≤ s ≤ 50%; (3) The pulse width of the pulse current is 1ms to 50ms; (4) The distance between the cathode electrode and the anode electrode is 15mm~20mm; (5) The deposition temperature is 45℃-60℃; (6) The deposition time is greater than or equal to 80s.
34. The preparation method according to claim 33, characterized in that, The electroplating method specifically includes periodically applying a pulsed current to the electroplating solution, causing copper ions in the electroplating solution to be reduced and deposited; wherein, the peak current density I of the pulsed current satisfies 100A / dm²≤I≤180A / dm², the duty cycle s of the pulsed current satisfies 2%≤s≤10%, and the deposition time is 80s-250s.
35. The preparation method according to any one of claims 22 to 34, characterized in that, The preparation method is a continuous production method.
36. A copper foil, characterized in that, The copper foil is prepared by the preparation method described in any one of claims 22 to 35.
37. The copper foil according to claim 36, characterized in that, The maximum width of the copper foil is greater than or equal to 1.5 meters, and / or the maximum length of the copper foil is greater than or equal to 10,000 meters.
Citation Information
Patent Citations
Negative current collector, negative pole piece and electrochemical device
CN110943228A
Nanotwin copper components
CN112941586A